“No More Separation between Zion and Her Children”: Palestine as a Sacred Geography and the Roots of the Gaza Genocide - Adam A. H. Yaghi (Arab Studies Quarterly)
This article maps out the Gaza genocidal rhetoric onto a genealogy of European-American imaginative re-makings of the geography of Palestine. This tradition, rooted in nineteenth-century visions of ethnically cleansing and repurposing the land according to colonial and theological worldviews, has systematically imagined freeing a barren Palestine from Palestinian barbarity, neglect, and spiritual corruption. This hegemonic tradition and its geographies of domination, however, have not gone unchallenged. Indeed, as a model – one rarely studied though, Ibrahim Fawal’s diasporic Palestinian novel On the Hills of God offers an alternate anti-colonial geography of resistance. To develop its claims, the article first uses a body of interdisciplinary scholarship to establish the genealogy and expose its genocidal spatial remapping of Palestinian geography. It, next, strategically resorts to On the Hills of God as an anti-colonial text that not only uncovers the Zionist destruction of a fairly harmonious multifaith local cultural geography in pre-1948 Palestine, but also captures traumatic memories of a nation currently besieged in its shrinking indigenous geography, exposes established hegemonic narratives, and charts a trajectory of resistance.